Teaching computer programming: A practical review - Begosso, Luiz Carlos; Rodrigues da Silva, Priscila (2013 IEEE Frontiers in Education Conference (FIE), 2013)
Recent developments in computer programming environments have been introduced to the academic community. Scratch is one of such environments which seek to offer innovation features as a support to teaching computer programming. This study reports on the results from a case study conducted with young students for teaching algorithms and programming.